Research on profile inversion controlling methods of multi-slug polymer alternative injection. Issue 2 (3rd March 2020) - Zheng, Ailing; Liu, Dehua; Shao, Yanlin
ABSTRACT: The development practice of polymer flooding shows that the injection profile easily inverses during the process of single slug polymer flooding. The low effective or ineffective circulation of abundant injecting water in high permeability layer, low producing degree of low permeability layer and large polymer volume have influenced the sweep efficiency and oil recovery of polymer flooding. In view of these questions, the alternative injection method of various viscosity polymer slugs is studied. This paper explains the theory of enhanced oil recovery of multi-slug polymer alternative injection. The experiment results show that the alternative injection of high and low viscosity polymer slugs has a better effect than single slug polymer flooding. The mobility differences between high-low permeability layers can be effectively reduced. For a multi-layer heterogeneous reservoir, there is an optimal alternative cycle. Reasonable slug size can not only inhibit dominant channel forming in high permeability layer but also can effectively produce low permeability layer and control profile inversion to a certain extent. This provides a technical support for studying the controlling methods of profile inversion.